2010
DOI: 10.3109/14767050903177169
|View full text |Cite
|
Sign up to set email alerts
|

Reference ranges for cervical length by transvaginal scan in singleton pregnancies

Abstract: CxL shortened throughout the pregnancy. The chart present 5th, 50th, and 95th centile, respectively, at 23 weeks of 20 mm, 36 mm, and 47 mm; at 28 weeks of 17 mm, 33 mm, and 43 mm; and at 34 weeks of 10 mm, 29 mm, and 43 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 25 publications
5
17
0
1
Order By: Relevance
“…We measured between 16 +0 and 21 +6 weeks of gestation, about 2–4 weeks earlier than most previous studies. It is known that CL gradually decreases with advancing gestational age . Both Salomon et al.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We measured between 16 +0 and 21 +6 weeks of gestation, about 2–4 weeks earlier than most previous studies. It is known that CL gradually decreases with advancing gestational age . Both Salomon et al.…”
Section: Discussionmentioning
confidence: 98%
“… and Silva et al. measured a difference of 2 mm between mean CL at 20 weeks vs. at 22 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of nomograms have shown that CL is independent of gestational age at the mid-trimester ultrasound ( Table 2). 5,10,11,21,[25][26][27][28][29] There is considerable variability between published ranges, indicating specific variability of normal CL within different populations. 4 This underscores the need for the development of a local reference range.…”
Section: Reference Rangesmentioning
confidence: 99%
“…The studies that have examined CL during pregnancy are thwarted by either of three significant limitations: first, they are mainly cross‐sectional and so not appropriate for follow‐up examinations; second, they assume a normal distribution of CL and third, they do not cover the whole gestation . The aim of the present study was to create longitudinal reference ranges and develop normograms for CL in all trimesters.…”
Section: Introductionmentioning
confidence: 99%